Using task-based instruction in an ESP course in the Computer Center at the University of Costa Rica = El uso de la Metodología Basada en Tareas en un curso de inglés con propósitos específicos en el Centro de Informática de la Universidad de Costa Rica - Córdoba Cubillo, Patricia María 1954-; Navas Brenes, César Alberto 1976- (2009)
This article presents the advantages of using Task-based Learning to help learners from the Computer Center at the University of Costa Rica infer the rule of the superlative form of adjectives in English. This group of learners was taking an ESP course that was team taught by two instructors. The course lasted four months, and the instructors covered four different units. It is important to mention that the methodology based on tasks help learners pay more attention or concentrate more on meaning than Task-based language learning is an approach in which learners concentrate more on meaning than on form. By doing this, students perform different communicative tasks, which happen to be more meaningful because they are close to the learners' reality, instead of doing form-based discrete exercises, which are usually decontextualized and meaningless because they do not see a reason to do them. In the lesson presented in this article, the Computer Center students were asked to express their own ideas, either orally or in a written mode, about the topic of the lesson, the superlative form of the adjectives in English.
Este artículo tiene como propósito presentar las ventajas de usar la metodología basada en tareas (Task-based Learning) para ayudar a un grupo de estudiantes del Centro de Informática de la Universidad de Costa Rica a inferir la reglay uso de la forma superlativa de los adjetivos en inglés Estos estudiantes recibían un curso de inglés con propósitos específicos impartido por dos docentes de inglés. El curso tuvo una duración aproximada de cuatro meses y se cubrieron cuatro unidades. Es necesario señalar que la metodología basada en tareas ayuda a los y las estudiantes a concentrarse más en el significado que en la forma. Al hacer esto, los y las estudiantes llevan a cabo diferentes tareas comunicativas que tienen más significado porque se asemejan más a sus actividades cotidianas que los ejercicios gramaticales tradicionales, los cuales la mayoría de veces son descontextualizadas e insignificantes. En la sección que se presenta en este artículo, los y las estudiantes del Centro de Informática expresaron sus ideas, oralmente o por escrito del tema gramatical: la forma superlativa de los adjetivos en inglés.
En Revista Actualidades Investigativas en Educación, vol. 9, no. 1 (enero-abril 2009)
Descripción basada en el contenido visto el 16 de enero, 2025